Sexual offenses and offenders theory, practice, and policy - Terry, Karen J. (Wadsworth Cengage Learning, 2013)
Examines the unique characteristics of sexual offenses and the resulting laws that pertain specifically to them, including the causes and treatment of sexual offenses as well as the policy implications of research outcomes.